High space efficiency compact chipless RFID tag with equidistance resonances - Ammar, Kholoud; Hussein, Amr; Attia, Mahmoud (International Journal of Engineering and Technology, 2018)
Radio Frequency Identification (RFID) technology provides non line-of-sight communication between the reader and the tag. This technology is widely used for various applications such as item tracking, security, access control, health care, short and long-range applications. RFID can be used as low cost data identification technology using radio waves between the RFID transmitter and the RFID receiver. Many attempts are introduced to implement the chipless RFID tags but they suffer from non-equal spacing between resonances which makes it difficult to make the decision. In this paper, compact low cost spectral signature based chipless 8-bits RFID tag is introduced. Multi dual-band resonating circuits with different resonances are used. The operation bandwidth is limited by the second resonance of the resonator. To avoid the presence of harmonics in the operating frequency range, multiple resonators with different shapes are introduced. The proposed tag instead of encoding only one data bit it encodes two data bits providing higher bits/resonator. The proposed tag provides equidistance between resonance frequencies. The tag is implemented on FR4 substrate of dielectric constant =4.4, thickness h=1.6mm and loss tangent Î´=0.0018. The scattering parameters Â of the fabricated tags are measured using the vector network analyzer (ROHDE&SCHWARZ ZVB 20). The designs of the tags are made using the software package CST MICROWAVE STUDIO.